iSAT, the new generation digital agro advisory tool that empowers farmers to manage climate risks - Joseph, Jacob Emanuel; Worou, Nadine; Diedhiou, Lamine; Dhulipala, Ram; Houessionon, Prosper; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
International Livestock Research Institute (ILRI) scientists collaborated with Jokolante, a Senegalese Agritech company, the Senegalese National Meteorological Agency (ANACIM) and the Regional Center for Improvement of Plant Adaptation to Drought (CERAAS) of the Senegalese Institute of Agricultural Research (ISRA) to develop a climate advisory service through a decision tree process known as iSAT, which is intended for smallholder crop and livestock farmers. The iSAT process builds context-specific and real time climate and agro-advisory informa tion available through ICT. As of September 2022, weekly climate informed agro-based advisories using IVR voice messages (18 994 in local languages-Wolof, Pula), which have been sent to 2720 (23.5% women-led farms) registered users via Jokolante. Climate informed agro-advisories developed with iSAT are now integrated into the SAIDA app (A Food and Agriculture Organization of the United Nations [FAO] tool for Senegal administered by the National Agency for Agricultural and Rural Council (ANCAR) with a potential national reach of 84,000 producers.